Seed dispersal by rhesus macaques Macaca mulatta in Northern India. Issue 12 (16th May 2014) - Sengupta, Asmita; McConkey, Kim R.; Radhakrishna, Sindhu
<x xml:space="preserve">Abstract</x> Frugivorous primates are important seed dispersers and their absence from forest patches is predicted to be detrimental to tropical forest regeneration and recruitment. With the reduction of primate populations globally, ecologically resilient primate species, characterized by dietary flexibility and the ability to thrive in a variety of habitats, assume new importance as seed dispersers. The most widely distributed non‐human primate, the rhesus macaque Macaca mulatta has been intensively studied but little is known about its role in maintaining ecosystem structure and functions. Due to their frugivorous diet, large group sizes, large home ranges and tolerance to disturbance, rhesus macaques may be effective seed dispersers. We studied seed dispersal by rhesus macaques at the Buxa Tiger Reserve, India, through a combination of behavioural observations and germination experiments. Rhesus macaques dispersed 84% of the 49 species they fed on either through spitting or defecation. Nearly 96% of the handled seeds were undamaged and 61% of the species for which germination tests were performed had enhanced germination. Almost 50% of the monitored seeds among those deposited in situ germinated and 22% established seedlings, suggesting that rhesus macaques are important seed dispersers in tropical forests. Due to their widespread distribution and large populations, rhesus macaques are perceived as common and are categorized as Least Concern on the IUCN Red List, effectively excluding them from any conservation plans. Based on the results of our study, we argue that rhesus macaques fulfill critical ecological functions in their habitat and that this parameter must be taken into consideration when they are reviewed for conservation priorities. Am. J. Primatol. 76:1175–1184, 2014. © 2014 Wiley Periodicals, Inc.